2023
DOI: 10.1002/adfm.202214339
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Synthesis, Intrinsic Properties and Optoelectronic Applications of Perovskite Single Crystals

Abstract: Metal halide perovskite have shown great potential for applications in photovoltaics, light‐emitting diodes and photon detectors, mainly owing to their superb optoelectronic properties, low‐cost raw materials and facile fabrication process. Although, polycrystalline perovskite thin‐films have been actively investigated for preparing various optoelectronic devices, the presence of detrimental defects at grain boundaries, serious ion migration and limited stability unfortunately hinder their device performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 197 publications
0
12
0
Order By: Relevance
“…The notorious ion migration in 3D Pb-based perovskites under a working electric field remains unsolved, which normally results in continuous dark current drift and a more significant polarization effect under higher bias. 93,149–153…”
Section: Application Of Halide Perovskites For X-ray Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notorious ion migration in 3D Pb-based perovskites under a working electric field remains unsolved, which normally results in continuous dark current drift and a more significant polarization effect under higher bias. 93,149–153…”
Section: Application Of Halide Perovskites For X-ray Detectionmentioning
confidence: 99%
“…Organic–inorganic hybrid lead-halide perovskite technology still suffers from low stability issues before further commercialization. 152 For instance, moisture and heat exposure can lead to rapid decomposition of halide perovskites. Choi et al observed the degradation process of hybrid perovskites in atomic-scale, and proposed the degradation was induced by the volatility of the organic component and inherent structural disorder.…”
Section: Application Of Halide Perovskites For X-ray Detectionmentioning
confidence: 99%
“…In addition, compared with lead-based perovskite SCs, the lead-free DP SCs have an obvious drawback that their sizes are relatively small and difficult to grow to the inch level, which inhibits their large-area and large-scale production and application. Interestingly, metal halide perovskite NCs not only effectively solve the above problems but also exhibit significant advantages over corresponding bulk SCs in terms of cost, transparency, flexibility, and miniaturized devices for X-ray detection. All-inorganic lead-based, cuprous-based, and manganese-based halide perovskite NCs can be blended with organic polymers, silica, or glasses to achieve highly efficient large-area X-ray imaging and detection. Unfortunately, the luminescence and scintillating properties of lead-free halide NCs can be seriously compromised compared to their single-crystalline, microcrystalline, and polycrystalline counterparts after nanocrystallization. Therefore, it is of great significance and challenge to develop high-performance 3D DP NCs; unravel the luminescence mechanism, scintillating property, and excited state dynamics; and apply them to optoelectronic applications.…”
mentioning
confidence: 99%
“…Chiral 2D organic–inorganic hybrid perovskites (OIHPs) represent an intriguing class of materials that combine the excellent crystallinity and exciton properties inherent in 2D perovskites, as well as the unique chiral optoelectronic and spintronic properties derived from its chirality. 1,2 The incorporation of chiral OIHPs into various optoelectronic systems presents exciting opportunities for advanced technologies in circularly polarized luminescence (CPL) detection spin modulation, nonlinear optics, bulk photovoltaics, ferroelectrics, and more. 3,4 However, the majority of reported chiral perovskites contain high concentrations of toxic lead ions and exhibit stability issues, which significantly impede their feasibility for large-scale production and practical use.…”
mentioning
confidence: 99%
“…7,8 Inevitably, the challenges associated with the utilization of corrosive acid solutions and the resulting pollution, as well as the stringent requirements for temperature control and time-consuming processes in single crystal growth, pose significant obstacles to large-scale production. 1 Additionally, the resultant single crystals often exceed the nanoscale in size, lacking desirable colloidal dispersity and solution processability, limiting the detailed investigation of size and structure-dependent characteristics of chiral perovskite nanomaterials. 9 Fortunately, colloidal 2D halide perovskites can be conveniently prepared by an organic antisolvent to impart supersaturated precipitation caused by solubility changes, eliminating the requirement for heating and hydrohalic acids.…”
mentioning
confidence: 99%